Addressing White Supremacy on Campus Anti-Racist Pedagogy and Theological Education - Montano, Steffano (2019)
Students in colleges and universities across the United States are being exposed to overtly white supremacist groups on campus. These groups dub themselves "identitarians" and attempt to influence students to support a white nationalist ideology through claims of reverse racism that threaten the lives of people of color. Theologically, this ideology also presents an obstacle for instruction: the existence of a competing Imago Dei that ties itself to white supremacy, dehumanizing persons of color. This article encourages the use of anti-racist pedagogies in theological education as a corrective to this competing Imago Dei.